2001
DOI: 10.1023/a:1013290826504
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Autism is a pervasive developmental disorder of unknown etiology. It is likely caused by mutations in one or more genes. One approach to understanding the molecular changes that occur in autism is to measure gene expression in post-mortem brain samples from individuals diagnosed with autism. This may be accomplished with techniques such as cDNA microarrays or subtractive hybridization. In general, gene expression is regulated as a function of body region, developmental time, and physiological state. A premise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this study, we first generated Nsf +/- mice and found that the mice showed core ASD symptoms, such as abnormal sociability and communication, repetitiveness, and anxiety. Additionally, these mice showed decreased membrane expression of SERT and AMPA receptors in the brain, which were hound in ASD patients ( Purcell et al, 2001a ; Nakamura et al, 2010 ; Iwata et al, 2014 ). The mice also showed impaired PSD and LTD in the hippocampal CA1 region.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we first generated Nsf +/- mice and found that the mice showed core ASD symptoms, such as abnormal sociability and communication, repetitiveness, and anxiety. Additionally, these mice showed decreased membrane expression of SERT and AMPA receptors in the brain, which were hound in ASD patients ( Purcell et al, 2001a ; Nakamura et al, 2010 ; Iwata et al, 2014 ). The mice also showed impaired PSD and LTD in the hippocampal CA1 region.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, a decrease in the synaptic GluA1-3 receptor density may reflect a reduction in GluA2 levels in the postsynaptic membrane. In ASD patients, partial loss of NSF transcription and reduced SERT and GluA2 expression at the membrane surface without a decrease in their expression at the mRNA level have been reported ( Purcell et al, 2001a ; Nakamura et al, 2010 ; Iwata et al, 2014 ). The Nsf +/- mouse is a unique model that recapitulates the molecular abnormalities observed in ASD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) has shown the structural abnormalities in relevant brain structures such as the amygdala, cingulated anterior cortex, and cerebellum (Uddin and Menon, 2009 ). These alterations seem to be associated with neurotransmitters dysregulation with the imbalance between excitation and inhibition in neural circuits (Purcell et al, 2001a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA transcripts undergo several processing steps occurring first in the nucleus, then in the cytoplasm where the mature 22–25 nucleotide-long miRNA [17], [18] enacts mRNA translational repression or cleavage by binding to the 3′-untranslated region of their respective target mRNAs [19]. Only a few studies have investigated the ASD transcriptome in post-mortem brain samples, so far [20][22]. Other studies have used mRNA from lymphoblastoid cell lines or peripheral blood cells isolated from patients [23][26].…”
Section: Introductionmentioning
confidence: 99%